2021
DOI: 10.1097/pxr.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 restrictions on physical activity and quality of life in adults with lower limb amputation

Abstract: Background: This study investigated the impact of COVID-19 restrictions on ambulatory activity and health-related quality of life (HR-QoL) in people with a lower limb amputation (LLA) in Norway. We hypothesized that the restrictions would negatively affect HR-QoL and decrease prosthetic wear time and ambulatory activity in participants with already limited mobility. Methods: Twenty individuals with LLA (age and time since amputation 56.2 6 11.9 and 22.3 6 20.1 years, respectively) participated. Ambulatory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The most frequently used wearable technologies were the StepWatch (Modus Health, Edmonds, Santa Monica, CA, USA) [ 4 , 21 , 25 , 27 , 28 , 30 , 42 , 44 , 46 , 48 , 49 , 50 , 51 , 54 , 57 , 58 , 61 , 64 , 65 , 69 , 73 , 77 , 78 , 79 , 84 , 86 , 87 , 88 , 89 , 90 , 94 , 95 , 96 , 98 , 100 , 101 , 110 , 114 , 115 , 116 ], ActiGraph (ActiGraph, Pensacola, FL, USA) [ 29 , 31 , 32 , 39 , 41 , 43 , 45 , 47 , 53 , 70 , 75 , 80 , 81 , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most frequently used wearable technologies were the StepWatch (Modus Health, Edmonds, Santa Monica, CA, USA) [ 4 , 21 , 25 , 27 , 28 , 30 , 42 , 44 , 46 , 48 , 49 , 50 , 51 , 54 , 57 , 58 , 61 , 64 , 65 , 69 , 73 , 77 , 78 , 79 , 84 , 86 , 87 , 88 , 89 , 90 , 94 , 95 , 96 , 98 , 100 , 101 , 110 , 114 , 115 , 116 ], ActiGraph (ActiGraph, Pensacola, FL, USA) [ 29 , 31 , 32 , 39 , 41 , 43 , 45 , 47 , 53 , 70 , 75 , 80 , 81 , …”
Section: Resultsmentioning
confidence: 99%
“…Of the 46 included observational studies, 13 studies aimed to describe characteristics of real-world behavior [ 21 , 26 , 33 , 40 , 60 , 63 , 66 ], real-world measurements in a specific population [ 44 , 50 , 62 ], or at a specific moment in time, such as post-rehabilitation [ 21 , 45 , 50 ], or during a mountaineering expedition [ 59 ]. Four studies observed changes in real-world behavior over time, including changes between before and during the COVID-19 pandemic [ 24 , 27 ], during in-patient and leave periods [ 36 ], and before and after prosthetic disuse [ 25 ]. One study investigated the effect of various prosthetic accommodation durations [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations